International variation in childhood cancer mortality rates from 2001 to 2015: Comparison of trends in the International Cancer Benchmarking Partnership countries - Smith Lesley; Stiller Charles A.; Aitken Joanne F.; Hjalgrim Lisa L.; Johannesen Tom; Lähteenmäki Päivi; McCabe Martin G.; Phillips Robert; Pritchard-Jones Kathy; Steliarova-Foucher Eva; Winther Jeanette F.; Woods Ryan R.; et al. (WILEY, 2025)
Despite improved survival rates, cancer remains one of the most common causes of childhood death. The International Cancer Benchmarking Partnership (ICBP) showed variation in cancer survival for adults. We aimed to assess and compare trends over time in cancer mortality between children, adolescents and young adults (AYAs) and adults in the six countries involved in the ICBP: United Kingdom, Denmark, Australia, Canada, Norway and Sweden. Trends in mortality between 2001 and 2015 in the six original ICBP countries were examined. Age standardised mortality rates (ASR per million) were calculated for all cancers, leukaemia, malignant and benign central nervous system (CNS) tumours, and non-CNS solid tumours. ASRs were reported for children (age 0-14 years), AYAs aged 15 to 39 years and adults aged 40 years and above. Average annual percentage change (AAPC) in mortality rates per country were estimated using Joinpoint regression. For all cancers combined, significant temporal reductions were observed in all countries and all age groups. However, the overall AAPC was greater for children (-2.9; 95% confidence interval = -4.0 to -1.7) compared to AYAs (-1.8; -2.1 to -1.5) and adults aged >40 years (-1.5; -1.6 to -1.4). This pattern was mirrored for leukaemia, CNS tumours and non-CNS solid tumours, with the difference being most pronounced for leukaemia: AAPC for children -4.6 (-6.1 to -3.1) vs AYAs -3.2 (-4.2 to -2.1) and over 40s -1.1 (-1.3 to -0.8). AAPCs varied between countries in children for all cancers except leukaemia, and in adults over 40 for all cancers combined, but not in subgroups. Improvements in cancer mortality rates in ICBP countries have been most marked among children aged 0 to 14 in comparison to 15 to 39 and over 40 year olds. This may reflect better care, including centralised service provision, treatment protocols and higher trial recruitment rates in children compared to older patients.